2005
DOI: 10.1063/1.2130147
|View full text |Cite
|
Sign up to set email alerts
|

The nature of the light scalar mesons

Abstract: Despite the apparent simplicity of meson spectroscopy, light scalar mesons cannot be accommodated in the usual qq structure. We study the description of the scalar mesons below 2 GeV in terms of the mixing of a chiral nonet of tetraquarks with conventional qq states. A strong diquark-antidiquark component is found for several states. The consideration of a glueball as dictated by quenched lattice QCD drives a coherent picture of the isoscalar mesons.Pacs: 12.39.-x,12.38.-t 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…[210,211] while -just as in our study -the same resonance was found to be compatible with an excited qq state in Ref. [102]. according to Eq.…”
Section: B Masses Of the Excited Statessupporting
confidence: 87%
See 1 more Smart Citation
“…[210,211] while -just as in our study -the same resonance was found to be compatible with an excited qq state in Ref. [102]. according to Eq.…”
Section: B Masses Of the Excited Statessupporting
confidence: 87%
“…Excited mesons were a subject of interest already several decades ago [97,98]; to date, they have been considered in a wide range of approaches including QCD models / chiral Lagrangians [99][100][101][102][103][104], Lattice QCD [105][106][107][108][109][110], Bethe-Salpeter equation [111][112][113][114], NJL Model and its extensions [115][116][117][118][119][120][121][122][123][124][125], light-cone models [126], QCD string approaches [127] and QCD domain walls [128]. Chiral symmetry has also been suggested to become effectively restored in excited mesons [129,130] rendering their understanding even more important.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, f 0 (1760) was identified as the state with the largest glueball component [1186]. The scheme can be extended to contain not only qq mesons and glueballs but also tetraquarks [1169,1187] and/or hybrids [1176]. The possible discovery of a further scalar meson at 1810 MeV/c 2 was suggested to require the extension into one of these directions [1188].…”
Section: Glueball-qq Mixing Scenariosmentioning
confidence: 97%
“…First of all we center our attention on the light scalar-isoscalar mesons. In [18] scalar mesons below 2 GeV were studied in terms of the mixing of a chiral nonet of tetraquarks with conventional q q states using the scheme described in Section 2.8.. We show in Table 8 results for the energies and dominant flavor component of the scalar-isoscalar mesons when considering also the mixing with a scalar glueball based on intuition from lattice QCD [30,31,32,33]. The results show a nice correspondence between theoretical predictions and experiment.…”
Section: Probabilities In Four-quark Systemsmentioning
confidence: 84%
“…A sketch of these mixing interactions is drawn in Figure 3. Such approach has been used in a series of papers to describe the light-scalar mesons and the open-charm and open-bottom meson sectors [17,18,19,20].…”
Section: Figurementioning
confidence: 99%